الأخطاء الشائعة في كتابة اللغة العربية للمادة الخط والإملاء وتحليلها لطالبات المدرسة التأهيلية بمعهد سلفية شافعية سوكرجو سيتوبندو جاوى الشرقية - Muhammad Kholison (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
تحليل الأخطاء (Error analysis) Error analysis is one of the applicable language disciplines that can be used to determine the level of language errors of a student when learning a foreign language, in this case is Arabic Language. تحليل الأخطاء '(Error analysis) is important to be carried out by teachers, such as teachers who teach the subject matter of al-Khath wa al-Imla', in order to determine students' abilities in writing Arabic, so that with Error analysis they can analyze student errors and then determine teaching materials and learning methods, what he will do. The results of this study are that the errors that occur in the Arabic writing of the students are divided into two, namely: 1) الأغلاط (errors) that fall into the Aghlath Error category (الغلاط), for example, writing the letters incorrectly because the sound is not clear, or students are less focused in hearing what the teacher says, 2) الأخطاء that fall into the Akhto mistakes category are errors caused by students' missunderstanding of language rules, for example two words that should be separated, joined, words that should start with أل, don't use أل